HUBUNGAN ANTARA BERMAIN MUSIK DENGAN KEMAMPUAN BERPIKIR KREATIF ANAK USIA DINI(Penelitian di Kelompok B RA Al-Kautsar Kecamatan Panyileukan Kota Bandung) - Ayuni Niwang Nastiti (ADIBA : JOURNAL OF EDUCATION, 2025)
The purpose of this study is to analyze the relationship between playing music and creative thinking skills in early childhood (Research in Group B RA Al-Kautsar, Panyileukan District, Bandung City). This study uses a quantitative approach with a correlational descriptive method, with two variables, namely Playing Music and Early Childhood Creative Thinking Ability, the data collection technique carried out is using questionnaires. The respondents in this study were 13 students in group B at RA Al-Kautsar, Panyileukan District, Bandung City. The data analysis carried out was in the form of research instrument tests (validity tests and reliability tests), partial analysis per indicator, prerequisite tests (normality tests and linearity tests), and hypothesis tests (correlation tests, determination coefficient tests). The results of the study showed that the relationship between Playing Music and Creative Thinking Ability in Group B RA Al-Kautsar, Panyileukan District, Bandung City was included in the category of positive and significant relationships. It is evidenced by the value of the partial analysis of the Happiness Indicator 3.46, Student Attraction 3.54, Student Attention 3.56 and Student Engagement 3.56 from the Interval of 3.1 – 4.00, and also supported by the Partial Analysis of the Fluency Indicator 3.62, Flexibility 3.59, Authenticity 3.49, Elaboration 3.44 from the Interval 3.6 – 4.00, as well as a significance value of 0.000 < 0.05 and a Pearson correlation value of 0.976 which is included in the category of strong correlation and does not have negative properties. In addition, based on the results of the R Square test (determination coefficient), a result of 0.952 was obtained which showed that the contribution of the independent variable (playing music) to the dependent variable (creative thinking ability) was 95.2%.